2005
DOI: 10.1111/j.1600-0722.2005.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble‐induced detachment of coadhering oral bacteria from salivary pellicles

Abstract: The presence and maturity of the salivary pellicle influences microbial adhesion and its tenacity in the oral cavity, posing a challenge to different plaque-control systems. Some plaque-control systems rely on surface-tension forces arising from passing microbubbles sprayed over the pellicle. Passage of such bubbles is accompanied by a high fluid flow, but systematic studies are lacking on the contribution of fluid flow vs. microbubbles towards plaque removal. Therefore, the aim of this study was to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Previous studies suggested that microbubbles were ineffective for adhering coaggregates 6,7) . However, the microbubbled water was found to have a signifi cantly higher removal effect on the biofi lms present on plastic than it did on tap water.…”
Section: Biofi Lm Removal Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that microbubbles were ineffective for adhering coaggregates 6,7) . However, the microbubbled water was found to have a signifi cantly higher removal effect on the biofi lms present on plastic than it did on tap water.…”
Section: Biofi Lm Removal Testingmentioning
confidence: 99%
“…Recently, microbubbled water has been used in several technical applications, including the decomposition of organic chemicals, wastewater treatment, medical technology and food processing [1][2][3][4][5][6][7] , however, it has not yet been applied in the fi eld of dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that if sufficiently high fluid shear stress can be generated, this alone can stimulate biofilm detachment (Rutter and Vincent, 1988;Hope et al, 2003;Sharma et al, 2005a;Paramonova et al, 2009). High-velocity water droplets (Cense et al, 2006) and entrained air bubbles (Parini et al, 2005;Sharma et al, 2005b) have also been shown to be able to remove bacteria and biofilms from surfaces utilizing the additional effect of generating a "surface-tension force" away from the surface by the passage of an air/water interface (Gómez-Suárez et al, 2001). An advantage of using fluid forces to remove biofilms is that mechanical forces can be projected beyond the device itself, by generating currents in the fluid surrounding the teeth by powered brushing (Adams et al, 2002) or through the generation of water jets by oral irrigation (Lyle, 2011).…”
mentioning
confidence: 99%
“…This indicates that microbubbled water has the effect on the tooth surface in a clinical situation. A previous study also showed that microbubbles were very effective to remove S. oralis from the glass plate [19][20] . Therefore the microbubbled water has the potential to prevent dental caries in the mouth of orthodontic patients.…”
Section: Discussionmentioning
confidence: 88%
“…There are only a few reports on the removal of microorganisms in dentistry. Sharma et al [19][20] reported that Streptococcus oralis was completely removed from salivary pellicles with microbubbled water but Actinomyces naeslundii was not completely removed. No report has so far examined the effect of microbubbled water on the removal of major oral pathogens such as S. mutans and C. albicans, which are among the major components of biofilms attached to orthodontic appliances.…”
Section: Introductionmentioning
confidence: 99%